Cellular and humoral mechanisms of osteoclast formation and bone resorption in Gorham-Stout disease. - Hirayama, T; Sabokbar, A; Itonaga, I; Watt-Smith, S; Athanasou, N (2001)
Gorham-Stout disease (GSD) is a rare, massively osteolytic condition which is associated with increased vascularity and an increase in osteoclast numbers. To determine the cellular and humoral mechanisms underlying the increase in osteoclast numbers and osteolysis in GSD, this study analysed circulating osteoclast precursor numbers and sensitivity to osteoclastogenic factors in a GSD patient and age/sex-matched controls. Monocytes were cultured with M-CSF (25 ng/ml) and RANKL (30 ng/ml) and osteoclast formation was assessed in terms of the formation of TRAP(+) and VNR(+) multinucleated cells and the extent of lacunar resorption. There was no increase in the proportion of circulating osteoclast precursors in GSD relative to controls, but lacunar resorption was consistently greater in GSD monocyte cultures. Increased osteoclast formation in GSD was noted when monocytes were incubated with IL-1beta (1 ng/ml), IL-6/sIL-6R (100 ng/ml), and TNFalpha (10 ng/ml). An increase in osteoclast differentiation and bone resorption was also noted in control monocyte cultures in the presence of GSD serum. These results indicate that the increase in osteoclast formation in GSD is due not to an increase in the number of circulating osteoclast precursors, but rather to an increase in the sensitivity of these precursors to humoral factors which promote osteoclast formation and bone resorption.